Further evidence of the heterogeneous nature of impulsivity. (April 2015) - Caswell, Amy J.; Bond, Rod; Duka, Theodora; Morgan, Michael J.
Highlights: Impulsivity is not a unitary construct and instead comprises dissociable subtypes. Reflection-impulsivity is a distinct and well-defined facet of impulsivity. Additional characterisations of motor-impulsivity are required. Several tasks purported to index impulsivity should be treated with caution. Researchers should employ multiple measures of types of impulsivity simultaneously. Abstract: 'Impulsivity' refers to a range of behaviours including preference for immediate reward (temporal-impulsivity) and the tendency to make premature decisions (reflection-impulsivity) and responses (motor-impulsivity). The current study aimed to examine how different behavioural and self-report measurements of impulsivity can be categorised into distinct subtypes. Exploratory factor analysis using full information maximum likelihood was conducted on 10 behavioural and 1 self-report measure of impulsivity. Four factors of impulsivity were indicated, with Factor 1 having a high loading of the Stop Signal Task, which measures motor-impulsivity, factor 2 representing reflection-impulsivity with loadings of the Information Sampling Task and Matching Familiar Figures Task, factor 3 representing the Immediate Memory Task, and finally factor 4 which represents the Delay Discounting Questionnaire and The Monetary Choice Questionnaire, measurements of temporal-impulsivity. These findings indicated that impulsivity is not a unitary construct, and instead represents a series of independent subtypes. There was evidence of a distinct reflection-impulsivity factor, providing the first factor analysis support for this subtype. There was also support for additional factors of motor- and temporal-impulsivity. The present findings indicated that a number of currently accepted tasks cannot be considered as indexing motor- and temporal-impulsivity suggesting that additional characterisations of impulsivity may be required.